Lifestyles of german descendent population in the state of Espirito Santo: The ethnographic documentary prodution as anthropolagical research method - Lopes Santos Neves, Manuela (Guará Journal, 2015)
The Ethnographic Documentary Production Project seeks the realization of videos that are either focused investigate, record and document the lifestyles of German descent population living in isolated communities in the state of Espírito Santo. Project activities were initiated in 2014 and involved students of Social Communication courses and Music of the Federal University of Espírito Santo (UFES) and young stu dent of the Mata Fria community in Afonso Cláudio. The objective was to not only provide an opportunity for students to put into practice the lessons learned in the classroom, but also stimulate the community’s young people to develop a view of themselves, their place and their life through the audiovisual language.
Keywords: Language and audiovisual production; Anthropology image; Teaching and learning; Germanic communities in Espírito Santo